Ethnic identity or something else? The production and use of non-ferrous dress-accessories and related items from early medieval Lincoln - Ten Harkel, A (School of Archaeology, Oxford University, 2018)
This paper asks, what can decorative metalwork tell us about the way in which identities were expressed in Viking-Age Lincoln? It presents the non-ferrous metalwork material from early medieval Lincoln, England (c. AD 800-1100), for the first time as a coherent assemblage. The artefact types – mainly dress-accessories and related decorative objects – are described in terms of their art-historical and stylistic characteristics, and placed within the context of manufacturing evidence from Lincoln. The question is asked, did the production of decorative metalwork play a key role in the deliberate creation or manipulation of ‘ethnic’ identities? Many of the objects found in Lincoln reveal Anglo-Saxon, Scandinavian, Hiberno-Norse and Frankish influences, and provide insights into the complex identities of Lincoln’s ninth- to eleventh-century inhabitants on multiple levels. However, the manufacturing evidence, providing an insight into the deliberate choices that were made by Lincoln’s metalworkers with respect to the manipulation of such identities, suggests that ethnic considerations may perhaps have been less important than is sometimes assumed.